Optimising The Role Of Local Government In Efforts To Minimise Premarital Sexual Behaviour Among Teenagers In Ratu Agung Sub-District, Bengkulu City - Firmansyah, M. Rozak; Alexander, Alexander; Dani , Rahiman (Social Sciences Journal, 2024)
Adolescence is a very decisive period because during this period children experience many changes in their psyche and physique. Premarital sexual behavior in adolescents tends to continue to increase, therefore researchers conducted a study entitled Optimizing the Role of Local Government in Efforts to Minimize Sexual Behavior. The formulation of the problem in this study is how to optimize the role of the Local Government in efforts to minimize premarital sexual behavior in adolescents in Ratu Agung District, Bengkulu City. The purpose of this study was to determine how to optimize the role of the local government in minimizing premarital sexual behavior in adolescents in Ratu Agung District, Bengkulu City. The research approach used in this study is a qualitative approach. The results of the study of Optimizing the Local Government of Ratu Agung District in socializing premarital sexual behavior in adolescents are as follows: socialization, conducting socialization in religious study groups, conducting socialization in schools, rejection of underage prospective brides in synergy with other agencies. internal in the form of supporting facilities and infrastructure and budgeting for guidance activities so that this can encourage the implementation of various work programs to be carried out properly. The conclusion of this study is that the optimization of the Ratu Agung sub-district government in minimizing premarital sexual behavior in adolescents is as follows: socialization, conducting socialization in religious study groups, conducting socialization in schools, rejection of underage prospective brides in synergy with other agencies.